English Teachers’ Creativity in Designing Differentiated Learning Materials for Senior High School Students - Rahmania, Rahmania; Noni, Nurdin; Talib, Ahmad (Journal of Excellence in English Language Education, 2026)
This study was conducted to explore the creativity of English teachers in designing differentiated learning materials for senior high school students. The research was motivated by the fact that many teachers still rely on traditional methods, such as lectures, which are considered less effective in fostering students’ motivation and enthusiasm for learning. In reality, teachers are expected to be innovative in creating teaching materials that are engaging, aligned with students’ learning styles, and capable of improving their understanding of the subject matter. A descriptive qualitative method was employed in this research, utilizing interviews and documentation of teaching materials in the form of modules. The participants were two English teachers from SMAN 2 Makassar and SMAN 8 Makassar. The findings revealed that both teachers demonstrated creativity in designing differentiated learning materials by making use of Canva. Through this platform, they successfully addressed students’ varying levels of readiness and learning styles by producing visually appealing and interactive materials. In summary, the teachers involved in this study exhibited a high level of creativity in developing instructional materials. This was evident in their use of digital media during the preparation of content, as further supported by the documentation collected throughout the research.